PENGARUH KONSENTRASI BAHAN PENGAW ET PADA KAYU MAHONI DENGAN BERBAGAI KONDISI TERHADAP SERANGAN RAYAP KAYU KERING DI PT. YOGYA INDO GLOBAL - , MELA HERLINA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Human need for wood raw material increases with the development of science and technology. However, the supply of wood with high durability more limited so it needs to be utilized timber with low durability. One type of wood that is widely used in the timber industry is the type of wood Mahogany (Swietenia macrophylla). Mahogany is the type with low durabil ity. Therefore, to improve quality of mahogany wood is required preservation efforts. There are two wood conditions that used . They are recycle wood and new wood. Type of preservative used is Deltamethrin Wood Protectant. The purpose of this study was to determine the effect of the conditions of wood and the optimal concentration of preservatives in mahogany wood preservation to prevent dry wood termite attack Cryptotermes cynocephalus Light. Wood used in the study is mahogany (Swietenia macrophylla King) measuring 5 x 5 x 3 cm with the condition of used and new and preservative used is Deltamethrin Wood Protectant. Pickling is done with solvent water at a concentration of 0.1%, 0.2%, and 0.3% at 2 conditions of wood. Sample immersed in a preservative solution for 30 minutes. Furthermore, testiny of sample to determine value of absorption and retention, then mounted tubes with a diameter of Â± 3 cm and Â± 4 cm a height and is fed on dry wood termites. Each tube is filled 50 fed dry wood termites. The attack corned to find out the value of termite mortality, weight loss, the degree of demage, and to determine the effectivenciss of preservatives during 4 weeks. The results showed that the interaction between wood conditions and concentration show a significant influence on actual retention, but has no affect the absorption, termite mortality, weight loss, and the degree of damage. In this study, the interaction between two wood conditions and preservative concentration of 0.1% already provide effective results to inhibit the activity of dry wood termite attack Cryptotermes cynocephalus Light on wood mahogany (Swietenia macrophylla King) with a value of 100% termite mortality.